Kenajisan Babi dan Hewan Buas serta Mekanisme Penyuciannya (Studi Komparasi Mazhab Malikī dan Mazhab Syafi’ī) - Jahada Mangka; Ronny Mahmuddin; A. Nasruddin (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2024)
This research aims to determine the status of impurity of pigs and wild animals and the mechanism of their purification from the perspective of the Malikī school and the Shafi'ī school of thought. This research is a type of library research, namely research carried out by collecting data from books or literature from previous research. This research was carried out by collecting data from searches or other writings, both from primary data sources and secondary data sources, as well as other literature related to the impurity of pigs and wild animals and their purification mechanisms. The results of the research found are as follows: first, the Malikī school and the Shafi'ī school of thought differ regarding the impurity of pigs and wild animals. The Malikī School says that pigs and wild animals are pure animals when they are alive, but when they are dead they are still considered unclean, the Shafi'ī School says that pigs and wild animals are unclean animals whether they are alive or dead. Second, the Malikī school and the Shafi'ī school of thought differ regarding the mechanism for purifying pigs and wild animals. The Malikī School says that the mechanism for cleansing pigs and wild animals is to use water without requiring the number of splashes and the use of soil or dust, the Syafi'ī School says that the mechanism for cleansing pigs and wild animals is that they must be washed seven times, one of which is using soil or dust. It is hoped that the implications of this research will be useful information for the general public, especially in understanding the impurity status of pigs and wild animals and their purification mechanisms from the perspective of the Malikī and Shafi'ī schools of thought. This information is important to increase public understanding of fiqh rules related to cleanliness and purity in Islam.